Early Alterations of Corneal Subbasal Plexus in Uncomplicated Type 1 Diabetes Patients. (2nd July 2019) - Schiano Lomoriello, Domenico; Abicca, Irene; Parravano, Mariacristina; Giannini, Daniela; Russo, Benedetta; Frontoni, Simona; Picconi, Fabiana
Abstract : Purpose . The purpose of our study is to describe the in vivo corneal confocal microscopy characteristics of subbasal nerve plexus in a highly selected population of patients affected by type 1 diabetes mellitus (T1DM) without any microvascular diabetes complications. Methods . We included 19 T1DM patients without diabetic peripheral neuropathy, diabetic autonomic neuropathy, diabetic retinopathy, and microalbuminuria. All patients underwent in vivo corneal confocal microscopy and blood analysis to determine subbasal nerve plexus parameters and their correlation with clinical data. We compared the results with 19 healthy controls. Results . The T1DM group showed a significant decrease of the nerve fiber length (P = 0.032 ), the nerve fiber length density (P = 0.034 ), the number of fibers (P = 0.005 ), and the number of branchings (P = 0.028 ), compared to healthy subjects. The nerve fiber length, nerve fiber length density, and number of fibers were directly related to the age at onset of diabetes and inversely to the duration of DM. BMI (body mass index) was highly related to the nerve fiber length ( r = −0.6, P = 0.007 ), to the nerve fiber length density ( r = −0.6, P = 0.007 ), and to the number of fibers ( r = −0.587, P = 0.008 ). No significant correlations were found between the corneal parameters and HbA1c. Conclusions . Early subclinical fiber corneal variation could be easily detected using in vivo corneal confocal microscopy, even in type 1 diabetes without any microvascular diabetes complications, including diabetic peripheral neuropathy, diabetic autonomic neuropathy, diabetic retinopathy, and microalbuminuria.